Berberine protects against gefitinib-induced liver injury by inhibiting the HMGB1/TLR4/NF-κB pathway - Zhang, Qiongyin; Li, Na; Ma, Xue; Qiu, Yue; Li, Chao; Chen, Ya (Frontiers in Pharmacology, 2025)
BackgroundGefitinib (GEF), a first-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) for non-small cell lung cancer (NSCLC), is frequently associated with drug-induced liver injury (DILI), thereby limiting its clinical application. This study aimed to evaluate the hepatoprotective effects of berberine (BBR) and explore the underlying mechanisms.MethodsIn vitro, human hepatocyte lines (THLE-2 and THLE-3) were exposed to GEF alone or in combination with HMGB1 siRNA, a TLR4 inhibitor, an NF-κB inhibitor, or varying concentrations of BBR to assess hepatotoxicity and the involvement of the HMGB1/TLR4/NF-κB pathway. In vivo, Sprague-Dawley (SD) rats were treated with GEF with or without different doses of BBR for 21 days. Liver injury and inflammatory responses were assessed, and pathway alterations were evaluated at both transcriptional and protein levels.ResultsGEF activated the HMGB1/TLR4/NF-κB pathway in vitro, increasing the levels of p-NF-κB p65, ALT, AST, and pro-inflammatory cytokines (INF-α, IL-1β and IL-6). BBR inhibited these effects in a concentration-dependent manner by suppressing pathway activation, reducing hepatotoxicity, and inhibiting HMGB1 nuclear-to-cytoplasmic translocation. In vivo, GEF induced weight loss, an increased liver-to-body weight ratio, elevated serum transaminases and pro-inflammatory cytokines, and histopathological liver injury, all of which were dose-dependently ameliorated by BBR co-administration. Moreover, BBR significantly downregulated the expression of HMGB1, TLR4, and NF-κB at both mRNA and protein levels in liver tissues.ConclusionGEF-induced liver injury is mediated by HMGB1-driven inflammation via the TLR4/NF-κB pathway. BBR provides dose-dependent hepatoprotection by targeting this pathway, suggesting a potential strategy to protect against GEF-induced liver injury among NSCLC patients.